(untitled) (CIPEEX, 2023)
The interest in analyzing green spaces in urban areas and correlating them with human health has expanded due to rapid urbanization, increased pollution, and growing trends of physical inactivity among the population. Considering the importance of preserving natural areas for promoting public health, the present study aimed to evaluate green spaces (green areas, vegetation cover, and vegetation cover percentage) in the Municipality of Itaberaí, Goiás. For this purpose, with the assistance of Geographic Information Systems (GIS) technology, the Green Area Index (GAI), the Vegetation Coverage Index (VCI), and the Vegetation Coverage Percentage (VCP) of the studied urban area were calculated. In the analysis of the IAV, the base map from Google Satellite in the QGIS 3.28.10 software was used; however, the ICV was measured using the Normalized Difference Vegetation Index (NDVI), calculated from images downloaded from the CBERS-4A satellite. With the application of the methodology in question, Itaberaí demonstrated that only 13.80% of its urban territory is covered by vegetation. Regarding the IAV, the study obtained a value of 1.32 m2/inhabitant, classified as very poor by the Brazilian Society of Urban Arborization (SBAU). Given the above, it is concluded that the urban area of Itaberaí requires special attention regarding the analyzed topic, as the city does not meet the internationally recommended levels of interurban vegetation.